Pengaruh Brand Ambassador, Brand Awareness, Dan Brand Image Terhadap Minat Masyarakat Dalam Berinvestasi Di Ajaib - Febi Ardhani; Rayhan Gunaningrat; R. Taufiq Nur Muftiyanto (Jurnal Manajemen Riset Inovasi, 2024)
The background to this research is that the author wants to know whether people have an interest in investing or not, especially in the Ajaib application. Apart from that, it aims to determine the influence of brand ambassador, brand awareness and brand image on people's interest in investing in Ajaib. The research method used is quantitative, with probability sampling as data collection. The number of respondents was 100 and data analysis used SPSS software. With the research results, brand ambassadors have no influence on investment interest, brand awareness has no influence on investment interest, and brand image has an influence on investment interest.